English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can someone give me the answer to it and the process how you got the answer? Alos, what is the problem called, the process. Right now I am learning trig and need future reference.

2006-10-13 07:23:53 · 9 answers · asked by Anonymous in Science & Mathematics Mathematics

Good answers guys...Thanks....

2006-10-13 07:54:40 · update #1

9 answers

You can use the basic algebra fact that
(x + y)^2 = x^2 + 2 x y + y^2

In this case, with x = sin t and y = cos t, you find
(sin t + cos t)^2 = (sin t)^2 + 2 sin t cos t + (cos t)^2

Note: mathematicians don't like parentheses so they write sin^2 t instead of (sin t)^2, etc.

It is a basic fact in trigonometry that the square of the sine plus the square of the cosine of the same angle are always equal to 1. In symbols: sin^2 t + cos^2 t = 1.

Therefore,
(sin t + cos t)^2 = (sin t)^2 + (cos t)^2 + 2 sin t cos t
... = 1 + 2 sin t cos t

Finally, the product (2 sin t cos t) is special because it is precisely the sine of *twice* the angle, that is,

2 sin t cos t = sin (2t)

Therefore, the expression simplifies as

(sin t + cos t)^2 = 1 + sin (2t)

as many others already pointed out...

2006-10-13 07:37:21 · answer #1 · answered by dutch_prof 4 · 2 0

The process is squaring a binomial. It follows the form:

(a+b)^2 = a^2 + 2ab + b^2

therefore,

(sin t + cos t)^2 = sin^2 t + 2 sin t cos t + cos ^2 t

however, by definition

sin ^2 t + cos ^2 t = 1

so, the result is

(sin t + cos t)^2 = 1 + 2 sin t cos t

2006-10-13 14:35:33 · answer #2 · answered by Anonymous · 0 0

=sin^2 t + 2 sintcost + cos^2 t
=1+2sintcost
=1+sin(2t)

2006-10-13 14:31:31 · answer #3 · answered by locuaz 7 · 1 0

(sin t + cos t)^2
=(sin t + cos t)(sin t + cos t)
=(sin t)^2 + 2.sin t.cos t + (cos t)^2
=1 + 2.sin t.cos t
=1 + sin 2t
[Note: (sin t)^2 + (cos t)^2 = 1 and 2.sin t.cos t = sin 2t]

2006-10-13 14:49:26 · answer #4 · answered by Anonymous · 0 0

=sin^2(t) + cos^2(t) + 2sin(t)cos(t)
=1+ 2sin(t)cos(t) as sin^2(t) + cos^2(t)=1

2006-10-13 14:38:41 · answer #5 · answered by Anonymous · 0 0

the first answer is right, and they are called trigonometric identities for your future reference.

2006-10-13 14:32:49 · answer #6 · answered by Anonymous · 0 0

=sin^2(t) + cos^2(t) + 2sin(t)cos(t)
=1+ 2sin(t)cos(t) bcoz sin^2(t) + cos^2(t)=1

2006-10-13 14:30:42 · answer #7 · answered by Mukesh K 1 · 0 2

sin^2t+cos^2t+2sintcost
=>1+2sintcost
=>1+sin2t

2006-10-13 14:26:09 · answer #8 · answered by raj 7 · 1 1

What is the question ???????

2006-10-13 15:07:50 · answer #9 · answered by gjmb1960 7 · 0 0

fedest.com, questions and answers